Kurikulum Bahasa Arab Di Pondok Pesantren Mahasiswa (Studi Deskriptif Kualitatif Kurikulum Bahasa Arab di Pondok Pesantren Mitra Institut Agama Islam Negeri Purwokerto) - Harimi, Abdal Chaqil (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2019)
Arabic is the core material in pesantren. Likewise also in the boarding school Mitra IAIN Purwokerto. The form of learning activities and presentation of the material is determined by the orientation of Islamic boarding schools to the understanding of Arabic itself. This paper discusses the Arabic language curriculum in Islamic boarding school students in Purwokerto with a focus on research objectives of learning Arabic, Arabic learning activities, and Arabic learning materials in five Islamic boarding schools namely Islamic boarding schools at Thohiriyah, Islamic boarding schools al-Hidayah, Islamic boarding schools and Najah, pesantren Qur'an al Amin, and Darussalam boarding school. After discussing and analyzing data, it can be concluded that two Islamic boarding schools still consider Arabic as a tool to understand the sources of Islamic studies, namely Islamic boarding schools at Thoriyah and Islamic boarding schools in the Qur'an Al-Amin. While the other three Islamic boarding schools namely al Hidayah boarding school, a Najah boarding school, and Darussalam boarding school combine basic Arabic (as a tool) and practical Arabic. However, all Islamic boarding schools have in common that is placing Arabic in their respective Madrasah Diniyah programs.